2016
DOI: 10.1093/glycob/cww009
|View full text |Cite
|
Sign up to set email alerts
|

FUT1genetic variants impact protein glycosylation of porcine intestinal mucosa

Abstract: A massive use of antibiotics in industrial pig production is a major cause of the rapidly rising bacterial resistance to antibiotics. An enhanced understanding of infectious diseases and of host-microbe interactions has the potential to explore alternative ways to improve pig health and reduce the need for antibiotics. Host-microbe interactions depend on host-expressed glycans and microbe-carrying lectins. In this study, a G > A (nucleotide 307) missense mutation in the porcine α1,2fucosyltransferase 1 gene (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
0
14
0
1
Order By: Relevance
“…To our knowledge, no study has tested the variability of FUT1 in the porcine mammary gland and we do not know if it is relevant for free OS composition in addition to O-glycans. Nevertheless, the hypothesis that different frequencies of detection of FL in different breeds could be associated with FUT1 variability is worth further consideration [25]. LNDFH was identified to deter the adhesion of several strains of norovirus in humans [26], a cause of diarrhoea in infants.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has tested the variability of FUT1 in the porcine mammary gland and we do not know if it is relevant for free OS composition in addition to O-glycans. Nevertheless, the hypothesis that different frequencies of detection of FL in different breeds could be associated with FUT1 variability is worth further consideration [25]. LNDFH was identified to deter the adhesion of several strains of norovirus in humans [26], a cause of diarrhoea in infants.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation on FUT1 leads to a higher expression of FUT1 and FUT2 and an increase in the activity of the enzyme in FUT1 GG pigs. This biological mechanism results in a different level of glycosylation on the protein structure of porcine ileum mucosa (Hesselager et al, ). In accordance with the immunohistochemistry observations of Coddens et al (), our work showed that the FUT1 AA had a lower immunoreactivity score for UEA than FUT1 AG and FUT1 GG and an opposite response for the PNA immunoreactivity both in brush border and goblet cell.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that MUC4 and FUT1 genotypes are not only associated with piglets susceptibility to PWD but can also influence the intestinal homoeostasis. For instance, healthy piglets with different MUC4 and FUT1 genotypes are known to differ for their intestinal microbial profile ( MUC4 , Messori, Trevisi, Simongiovanni, Priori, & Bosi, ; FUT1 , Poulsen et al, ) and for their intestinal protein glycosylation (Hesselager, Everest‐Dass, Thaysen‐Andersen, Bendixen, & Packer, ). Furthermore, the intestinal mucosa of piglets with the susceptible genotype ( MUC4 CG/GG ) had an up‐regulation of genes related to antimicrobial peptide and immune function such as lipopolysaccharide binding protein ( LBPI ) and regenerating islet‐derived 3 gamma ( REG3G) compared to pigs with a resistant genotype (Trevisi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The fucosylation of carbohydrate structures expressed on cell surfaces of the gut by glycoproteins, glycolipids, and proteoglycans have been associated with biological processes such as inflammation, host–pathogen interactions, and tumor metastasis [ 11 , 12 ]. A recent study by Hesselager et al (2016) showed that there are significant differences in the O-linked glycans of the intestinal mucosal proteins between FUT1 AA and FUT1 AG pigs [ 13 ]. The FUT1 AG lead a higher level of O-glycan structures that were fucosylated to show H-antigens [ 13 ].…”
Section: Introductionmentioning
confidence: 99%